Designing a low-cost WebGIS system for delivering land inforination via internet - Binh, Tran Quoc; Ha, Hoang Van; Thoa, Luong Thi; Hung, Nguyen Van (VNU Journal of Science: Earth and Environmental Sciences; Vol 25 No 3, 2009)
Abstract